Traditional knowledge on the use of local food crops by Togutil Ethnic in Halmahera Island, Indonesia - TAMALENE, M. NASIR (Society for Indonesian Biodiversity & Universitas Mulawarman, Samarinda, Indonesia, 2017)
Tamalene MN. 2017. Traditional knowledge on the use of local food crops by Togutil Ethnic in Halmahera Island, Indonesia. Asian J Agric 1: 66-72. Food crop is an important component in the life system of Togutil ethnic group in Halmahera Island. The main characteristic of the ethnic is their nomadic life despite the existence of some sedentary groups. Generally, the ethnic consumes wild food plants growing in their natural ecosystem. This paper presents selected result of food crop studies conducted in Halmahera Island Indonesia. The botanical supply of food crops of the ethnic has high usefulness in their social and cultural activities. Data was collected through in-depth interview method to key informants chosen based on purposive sampling. Plant species was identified in the Laboratory of Herbarium Botany Bogoriense of the Biological Research Center of Indonesian Institute of Science (LIPI). 48 species of 23 families of food crops are used by Togutil tribe of Halmahera Island Indonesia. The food crops identified were wild plants of 45.83% growing in bushes habitat and primary forest and cultivated crops of 56.25% planted in the garden and yard. Other uses of the food crops were as medicinal plant of 64.28%, house building of 29.17%, and handicraft and adhesive for animal of 4.17%. In the cultural aspect, food crops were used for hunting ritual, medium of exchange (barter), welcoming guest ritual and traditional ritual. The value of Cultural Food Significance Index (CFSI) in very high significance category was 64.58%, high significance was 27.08%, and low significance and very low significance are 4.16%.